DETERMINING THE CURRENT FINANCIAL POSITION OF A CITY. - Lorig, Arthur N. (The Accounting Review, 1941)
Abstract The article focuses on determining the current financial position of a city. Most of the expenditures of a municipality are inevitable and must be met. A city could not do without police and fire protection, sanitary and health service, relief, etc., even for a short time. It is also essential either to make cash provision through sinking funds for meeting long-term debt, or to retire serial bonds. These expenditures and provisions are just as much a demand upon current resources as are current liabilities. On the other hand, the listed current resources are not the only means of satisfying these demands. Some incomes, such as tax levies, fines, etc., are certain to bring cash into the treasury in the immediate future. They are a logical offset to current expenditure requirements and current liabilities. It is proposed, then, to regard the financial condition of a city as referring chiefly to its ability to meet all current requirements in the form of expenses, current liabilities, and provisions for meeting long-term indebtedness. Current financial position will be regarded as the ability of the city to meet its financial requirements in the immediate future. Particular emphasis should be placed upon the next year inasmuch as requirements are customarily determined for a period of a year.